Pyxine janakiae (Caliciaceae): A new lichen species from the Southern Western Ghats, India - Anilkumar, Aswathi; Christy, Arun; Sequeira, Stephen (Phytotaxa, 2025)
A new saxicolous lichen species, Pyxine janakiae, belonging to the family Caliciaceae is described from Mathikettan Shola National Park, Kerala, India. The new species is morphologically similar to Pyxine himalayensis but differs by the absence of pseudocyphellae on the thallus, an internal stipe that is brown to brownish orange with a white colouration in the lower region, and different TLC components.